Kinerja Pelayanan Akademik Di Fakultas Ekonomi Universitas Negeri Manado Dengan Model Balanced Scorecard - Hisky Ryan Kawulur (Tasharruf: Journal Economics and Business of Islam, 2018)
Balanced score card interpretes he importance of the main stakeholders including owners, customers and employees. The term balance reflects effort to capture both financial and non financial measurements emphasizing cause and effect indicators, long term goals of the company external and internal perspectives as well as subjectives quantitative and qualitative goals. The application of BSC in university so far, increase accountability to develop strategies, control existing opportunity and increase operational effort. The faculty of economy of the State university of Manado is one of the faculties with commitments to increase quality of academic services from both staff and teachers for students satisfaction. With this commitment the measurement of academic ethics is a must. This research aims to measure students satisfaction degrees on academic service at the faculty of economy of the state university of Manado by using balance Score card consisting of customers perspective, internal business, and development and learning towards quality service achievement. Keywords: Balance Score Card, Ethics Measurement, Academic Service